2010
DOI: 10.1002/aic.12455
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen mass transport limitations at the cathode of polymer electrolyte membrane fuel cells

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Oxygen transport across the cathode gas diffusion layer (GDL) in polymer electrolyte membrane (PEM) fuel cells was examined by varying the O 2 /N 2 ratio and by varying the area of the GDL extending laterally from the gas flow channel under the bipolar plate (under the land). As the cathode is depleted of oxygen, the current density becomes limited by oxygen transport across the GDL. Oxygen depletion from O 2 /N 2 mixtures limits catalyst utilization, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…In the numerical simulation of a whole cell, the y Oc distribution is calculated using a model describing mass transport primarily in the GDL and flow channel. 10 As y Oc is raised, the effects of oxygen convection appear greater. In the case of an air supply, a more typical y Oc value is 0.1-0.21, and F Conversely, a negative Peclet number represents an oxygen profile that is shifted toward the PEM side, resulting in an improved F ðCÞ e .…”
Section: Dimensionless Model Analysismentioning
confidence: 99%
“…In the numerical simulation of a whole cell, the y Oc distribution is calculated using a model describing mass transport primarily in the GDL and flow channel. 10 As y Oc is raised, the effects of oxygen convection appear greater. In the case of an air supply, a more typical y Oc value is 0.1-0.21, and F Conversely, a negative Peclet number represents an oxygen profile that is shifted toward the PEM side, resulting in an improved F ðCÞ e .…”
Section: Dimensionless Model Analysismentioning
confidence: 99%
“…46 Moreover, Benziger et al showed that for lower oxygen molar fractions in the cathode (which is the case with air feed) the dominant mode of transport is diffusion. 47 Nevertheless, this assumption needs to be revisited based on the operating condition and cell configuration. For instance, Weber et al found convective heat transfer to be significant.…”
Section: Mathematical Model Developmentmentioning
confidence: 99%
“…wv,GDL [47] At the membrane interface, the following conditions are imposed for the water vapor flow rate:…”
mentioning
confidence: 99%
“…6), indicating an increase in mass-transport resistance in cathode. For a DMFC operated with O 2 , convection is the main way for oxygen transport across the GDL, while for the one operated with air, diffusion is the dominant way for oxygen transport [27]. As a consequence, the overall performance of the cell fed with air is more sensitive to the changes in pore structures resulting from freeze damage than that fed with O 2 .…”
Section: Reversible Loss In Performancementioning
confidence: 99%